Industrial attachment report : Mobile Oil Singapore Pte Ltd, (12 Jan, 1999 - 26 Jun, 1999) - Tey, Boon Thai. (2008)
During the training, the student was attached to the Product Design Section, of the Technical department. By performing the role of a project engineer and through implementing management, quality control, negotiation and teamwork.